2019
DOI: 10.30867/action.v4i1.154
|View full text |Cite
|
Sign up to set email alerts
|

Intervensi media video berpengaruh pada pengetahuan dan sikap remaja putri dalam mencegah kurang energi kronik

Abstract: Community-based interventions to overcome chronic energy malnutrition among women of childbearing age and pregnant women can be done with communication, education, and information. Video can be useful for education purpose. The goal of this study was to determine whether video may have different effect to knowledge and attitude on preventing energy malnutrition among teenage girls compared to food model intervention. The Research a quasi experiment with pre-post test with control group design was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 3 publications
1
2
0
8
Order By: Relevance
“…So it can be concluded that there is an influence on the use of less chronic energy education models using web-based She Smart on knowledge in adolescent girls. This is in line with research conducted by Waryana et al (2019), which states the influence of providing counseling video media about the prevention of Chronic energy deficiency on the knowledge of adolescent girls. Likewise with research conducted by Norhasanah & Dewi (2021), states that there is an effect of providing balanced nutrition to knowledge in adolescents with Chronic energy deficiency.…”
Section: The Influence Of the Use Of Chronic Energy Deficiency Educat...supporting
confidence: 89%
See 1 more Smart Citation
“…So it can be concluded that there is an influence on the use of less chronic energy education models using web-based She Smart on knowledge in adolescent girls. This is in line with research conducted by Waryana et al (2019), which states the influence of providing counseling video media about the prevention of Chronic energy deficiency on the knowledge of adolescent girls. Likewise with research conducted by Norhasanah & Dewi (2021), states that there is an effect of providing balanced nutrition to knowledge in adolescents with Chronic energy deficiency.…”
Section: The Influence Of the Use Of Chronic Energy Deficiency Educat...supporting
confidence: 89%
“…In connection with this problem, several efforts can be made to prevent the risk of chronic energy deficiency in adolescence, one of which is by doing nutrition education (Evans,2008;Calderhead, 1989). Nutrition education needs to be provided to adolescents and mothers-to-be to increase knowledge or information early on about Chronic energy deficiency and efforts in dealing with it and increasing knowledge about their nutritional intake for example by consuming foods that source energy, protein, fat, vitamins, and minerals both of quality and quantity (Amalia et al, 2018;Syukur, 2017;Notoatmodjo, 2012;Wardhani et al, 2021;Waryana et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Oleh karena itu diperlukan upaya pemberian pendidikan kesehatan kepada kader, karena kader merupakan garda terdepan dalam peningkatan kesehatan pada masyarakat. Pengetahuan dapat dipengaruhi oleh pemberian informasi melalui video (Waryana, Sitasari and Febritasanti, 2019). Penyuluhan menggunakan media audio-visual cenderung lebih baik daripada menggunakan media cetak.…”
Section: Pendahuluanunclassified
“…11 Hadirnya media video yang merangsang 2 indera khususnya penglihatan dan pendengaran merupakan cara yang baik untuk memberikan pengetahuan yang lebih jelas kepada sasaran. 12 Disamping itu pada penelitian ini ditemukan juga bahwa media flipbook memiliki hubungan yang signifikan terhadap peningkatan pengetahuan tentang aktivitas fisik pada Mahasiswa FKM USU. Mahasiswa FKM USU dengan rerata nilai pada variabel pengetahuan yaitu 14,22 dan meningkat menjadi 22,39 dengan nilai probabilitas (p) = 0,001.…”
Section: Pembahasanunclassified